Peran Guru Dalam Menanamkan Perilaku Sopan Santun Pada Anak Usia Dini di TK Amarta Tani Bandar Lampung - N. Audine; Sulistianah Sulistianah; T. Dewantari; A. Tohir (Universitas Dehasen Bengkulu, 2023)
This study discusses the teacher's role in instilling polite behavior in early childhood. The purpose of this research is to describe the teacher's role in instilling polite behavior in early childhood at Amarta Tani Kindergarten. This research is a study using qualitative research data sources. Obtained from primary data and secondary data. Researchers obtained primary data from interviews with Class B teachers at Amarta Tani Kindergarten and observations of children's behavior related to polite behavior. Secondary data was obtained from the results of documentation, in the form of photos. The data obtained was then collected, reduced, described, tested for the validity of the data and concluded. the teacher makes a habit of greeting children every time they meet the teacher, the role of the teacher in teaching the teacher gives an example of respecting older people, the role of the teacher in planning the teacher exemplifies learning that accepts everything with the right hand, the role of the teacher in parenting the teacher gives directions so that children do not it is permissible to say harsh, dirty and arrogant words the role of the teacher in dealing with problems the teacher gives directions so that the child says thank you, sorry and please.